Transformations and Networks of Organizations: Systematic Access - Petružis, Gvidas; Tamošiūnas, Teodoras (Socialiniai tyrimai, 2019)
Relevance and problem of the study. The article analyses different approaches to organizational transformations and aims to systemize and summarize the existing theories of organizational transformations. Networks of organizations provide access to resources, knowledge and skills from other members of the network, network achievements can be distributed to all network participants. However, the network does not provide equal opportunities for all, mainly supporting those who invest more. Much is determined by different capabilities and abilities of network participants. For small business often find it difficult to become members of the network of organizations. This article therefore raises the scientific problem of how to increase the chances of small business becoming members of the network of organizations and gaining more rights in the activities of such a network. The objective of the paper is to systemize and summarize the scientific theories of organizations’ transformations and networks. Research methods: analysis, structuring, synthesis and comparison of research sources, logical categorization and classification, deduction, interpretation and justification of statements. The transformation of an organization is defined as the implementation of processes aimed at fundamental changes in the organization. Researchers in the organization’s transformations partially compare with the introduction of quality management systems in the organization and their functionality or the theory of the learning organization. The focus is on the dynamic ability of the organization can react flexibly and quickly to the changing internal and external environment. One of the main elements that determines the success of the transformation of the organization is the organization’s manager and his ability to develop his firm as learning organization. Organizations seeking to transform need good theoretical and practical knowledge of organizational transformations. Existing theories and methods are often divided into several types, but none of them is entirely appropriate. By combining several theories, they could provide a more comprehensive theory of the transformations of organizations and, at the same time, enable a better understanding of transformation processes. Science distinguishes four types of organizational transformations: from transformations, when they are managed easily due to the predicted environment, to the most complex scenario, where the environment is chaotic, difficult to predict and changes in the organization must respond more to a changing environment than planning. However, the transformation of an organization is a more planned process than chaotic, so transformation theories can be combined with quality management systems and learning organization theories. The transformation of the organization is highly dependent on the external environment: if the environment is calm and unchaotic, the entire transformation process of the organization takes place by combining short-term plans with the creation of a long-term vision and all this information transferring to the employees. When the transformation of an organization reaches a revolutionary, high level of destabilization, then external processes force organizations to become very flexible. The organization’s vision is then continually updated, and the organization’s ability to learn quickly is crucial. Scientists interpret the concept of networks of organizations differently. Each of the networks divides into internal and external ones, others focus on the assessment of network dynamics. There is consensus that the importance of networks of organizations is very high for all organizations working on market conditions. Networks of organizations make it possible to develop new products, to enter new markets, services and manufactured goods become better promoted compared to those organizations that do not participate in the networks of organizations. A small and medium-sized enterprise (SME) cooperation with a large enterprise creates opportunities for strengthening existing and developing new strategic resources. Both enterprises can strengthen each other by creating a long-term competitive advantage through strategic resources, i.e. to carry out the dissemination of co-produced products through joint logistics chains, to improve organizational cultures, to initiate changes in internal structures, strategies and management changes, integrating and developing organizational resources and traditional skills. SME see different objectives when participating in networks of organizations. SME’s networks help to ensure operational stability, improve efficiency, seek recognition. SME executives appreciate the benefits of participating in the network and need to have a lot of knowledge about the possible configurations of organizations’ networks in order to choose the most suitable for their business. Each SME aims to gain and maintain a long-term competitive advantage on the market. An organizational network enables SEM to troubleshoot major issues and use organizational network resources for own needs. It is suitable for those SMES that face great competition and are looking for ways to survive in the market and strengthen their competitiveness positions. However, to establish itself within an organizational network and acquire missing resources and new organizational competencies, SME face a number of challenges which are only overtaken by smart, flexible and collaborative SME.